Determining suitable ecotourism areas in protected watershed area through visibility analysis - Demir, Sara (Scibulcom Ltd, 2019)
The rapid population growth, technological improvement and the expansion the boundary of urban have affected the natural and cultural landscape values of rural areas negatively. This causes to consumption unawares natural and cultural values of landscape. Mary Valley protected watershed area, located in Macka, Trabzon, has one of the important national park, cultural heritage points, historical trails, river falls, natural forest views, wildlife and endemic plants was selected as a study area. Its landscape values have been damaged because of lack of administrative structure. This study aims to explore the natural and cultural landscape values and highlight the importance of cultural, historical and natural viewpoints of the Mary Valley. To achieve this goal, the natural and historical landscape data are collected and multi-criteria decision making methods, is employed on the basis of the data derived from the surveys and interviews with local and experts and then all data overlayed through visibility analysis process in GIS. Finally, 'very high-high and medium visibility areas' are offered as suitable ecotourism areas for ecotourism activities, which has no negative effects to natural and cultural areas. The findings can set guidance for sustainable for protected national and cultural values of watershed area in Turkey.
Keywords: ecotourism; environmental protection; GIS; multi-criteria decision making; protected watershed area